STRATEGIC POSITIONNING AND ORGANISATIONAL PERFORMANCE OF HOTELS IN PORT HARCOURT (World Bulletin of Management and Law, 2022)
This study sought to examine the effect of strategic positioning on organisational performance of Hotel in Port Harcourt, Rivers State, Nigeria. The study was guided by four research questions and it was hypothesized that there is no significant relationship between the strategic positioning (which comprises cost leadership and product differentiation) while organisational performance was measured by market share and profitability. A sample size of one hundred and eighty-two (182) respondents was drawn from 105 hotels in Port Harcourt using the cluster sampling technique. Pearson Moment Correlation Technique was used in testing the hypotheses at 95% level of confidence. It was found that there is a strong positive and significant relationship between cost leadership and product differentiation possessed a strong significant relationship with market share; boasting of r value of 0.889 and 0.901 respectively. Meanwhile they showed low correlation with profitability as they revealed r values of 0.512 and 0.473 respectively. The study found that traditional marketing technique is insufficient to drive organisational performance in today’s modern hotel business environment which is characterised with intense competition. To outperform competitors, the study recommends that hotel managers must strive to enhance their position in the minds of their target market by integrating cost leadership and product differentiating strategies into their marketing plan. However, these strategies should be implemented considering overall objective of the business and its unique environment. It is also imperative for hotel managers to take advantage of social media marketing platforms to create positive awareness and communication with the public. This will help boosts their position and ultimately induce higher patronage